Subjective Quality of Life of Women in the Perinatal Period: A Post Covid-19 Pandemic Exploration in North Macedonia - Bajraktarov, Stojan; Arsova, Slavica; Milutinovikj, Milosh; Mitrovska, Stefanija; Papestiev Aleksioska, Irena; Markova Daneva, Ana; Jovanovska, Viktorija; Filipche, Ana; Novotni, Ljubisha; Ivanovska Zafirova, Beti; Stoilkovska Blazhevska, Biljana; Fritzhand, Ana; et al. (Македонска академија на науките и уметностите, Одделение за медицински науки = Macedonian Academy of Sciences and Arts, Section of Medical Sciences/Walter de Gruyter GmbH, 2023)
Subjective quality of life could be considered one of the indicators of health behavior and wellbeing of women in the perinatal period. Accordingly, the aim of this paper was to examine how women in perinatal period perceive quality of life in various domains. Its relationship to age, number of pregnancies, course of pregnancies, and method of delivery and experience with Covid-19 pandemic was investigated, as well. Our sample consisted of 366 pregnant women in any period of pregnancy who came in for regular outpatient examinations and control, those who were hospitalized due to pathological pregnancy or due to the need for intensive care, as well as women in their postnatal period, one year after delivery, who were seeking professional advice from a gynecologist. The majority were aged 20 to 30 years (53.8%). The findings showed that assessed domains of subjective quality of life were related to a variety of experiences with the Covid-19 pandemic. The results are presented and discussed in detail. Implications and limitations are given, as well.